Three Level Inverter Based Unified Power Flow Controller, ISSN 1755-6398 - Berrahal, Khoukha; Bouhentala, Abd El Malik; Bensalem, Ahmed (International Journal of Power Electronics, 2020)
Unified power flow controller is a power electronics-based device utilised to improve transmission line capacity and control power flow transmitted by power transmission systems. This paper presents the application of the decoupled control strategy to control independently active and reactive power in the event of changes in the step points of the powers. Two types of controllers are used to handle the control strategy proposed: conventional PI regulator and fuzzy logic PI regulator. The fuzzy logic controller must have high performance to handle the problem of adjustment of power decoupling. Also, a three level neutral point controller inverter is used in both series and shunt parts of the UPFC to get multistep voltage wave and improve the power quality.